Features of puncture-dilated tracheostomy in elderly and senile patients - A. S. Ignatiev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Quite a lot of manuals have been published recently, both in paper and electronic form, on the relatively new technique of puncturedilated tracheostomy. However, it is almost impossible to find information about the features of this technique in elderly and old patients. And they are there and attract attention. For the first time in the article, we drew attention to the peculiarity of the anatomical structure of the neck and adjacent structures in elderly and old patients. A comparative table of mortality of patients with various techniques of tracheostomy is presented, which allows us to visually determine the most beneficial in elderly and old patients. The protocol of puncture-dilated tracheostomy in relation to elderly and old patients is presented.